A Preliminary Study On Pain Tolerance And Withdrawal Symptoms Among Active Ketum (Mitragyna Speciosa) Users In Malaysia - Abdul Rahim, Azlan (2022)
Kratom is known locally as ketum or biak (Mitragyna speciosa) in Thailand, Malaysia, and Indonesia. Southeast Asian countries are home to the ketum plant. Ketum leaves are extensively used as an herbal supplement (traditional medicine) for self-treatment of medical conditions in the West and Southeast Asia, including pain and opioid use disorder (OUD). However, ketum consumption over a prolonged period was associated with withdrawal effects. Therefore, to systematically investigate the effects of ketum based on claims from previous research (pain tolerance and withdrawal symptoms), a human laboratory study was conducted with 26 male participants in Pusat Sejahtera, Universiti Sains Malaysia (USM). The study aimed to investigate withdrawal symptoms using a validated clinical measurement, the Clinical Opiate Withdrawal Scale (COWS), after 12 hours of ketum cessation. Secondly, the study investigated ketum effects on pain tolerance using the cold pressor task. Study findings suggested no significant association between ketum consumption with withdrawal symptoms and pain tolerance. However, mild withdrawal symptoms were observed during the 12 hours of ketum cessation such as runny nose, yawning, restlessness and axiety.